Improving Learning Outcomes Through Cooperative Implementation Of Types tps With Concrete Tools In Mathematics Class VI SDN 025 Rokan IV Koto District - Ponijan Ponijan (Indonesian Journal of Basic Education, 2023)
Mathematics as one of the subjects taught in elementary schools functions to develop the ability to communicate using numbers, symbols, and aims to train ways of thinking systematically, logically, critically, creatively and consistently. Children are expected to be skilled at applying it in everyday life, but in reality, children experience many difficulties, especially in the ability to calculate the volume of geometric shapes. In order to improve the ability to calculate volume in elementary school, it can utilize learning resources around students in the form of concrete objects. By using concrete objects children are able to carry out logical activities in solving problems, that is a way to overcome learning problems at SDN 025 Rokan IV Koto. To achieve this goal, classroom action research was conducted in class VI of SDN 025 Rokan IV Koto. The data from this study were obtained by observation, interview and documentation methods. The results of the research show that (1) Through concrete objects around students, students' ability to interact can be improved so that the class atmosphere is lively. (2) Learning activities that give students freedom to manipulate learning resources, namely with concrete objects can increase the ability to calculate the volume of geometric shapes, and children are more active, creative. (3) Learning activities through concrete objects around students are in accordance with the character of learning mathematics, and in accordance with the readiness of the child's thinking so that the ability to calculate the volume of rectangular prisms and circular tubes can be improved